Education in Agricultural Health - Van Dijk, Frank J H; Van der Laan, Gert; Verberk, Maarten M; Colosio, Claudio (La Medicina del Lavoro, 2016)
IntroductionMore than one third of the world’s labour force is employed in agriculture, which is one of the most hazardous of all sectors and many agricultural workers suffer occupational accidents and ill health (5). In several parts of the world educational activities are developed, executed and evaluated (3) in order to protect the health and safety of agricultural workers. In September 2015 an international congress on Rural Health in Lodi, Italy, devoted a session1 to Education in Basic Occupational Health. The aims of this session were (1) exchange of recent experiences, and (2) discussion of potential future activities including the feasibility of an educational  network. Nine lectures, mentioned in the Appendix, were presented by experts from several countries and by representatives of ICOH, EU, ILO and WONCA2.[...]